Sensing Techniques for Food Safety and Quality Control. - Lu, Xiaonan (Royal Society of Chemistry, 2017)
Providing an updated summary of the application of different types of sensors for the analysis of food safety and quality, this book discusses the core principles, current research status, challenges and successful examples for each technology. -- Resumé vydavatele
Keywords: senzory; potravinářský průmysl; analýza potravin; bezpečnost potravin; kvalita potravin; sensors; food industry; food analysis; food safety; food quality; kolektivní monografie; elektronické knihy; collective monographs; electronic books